2018
DOI: 10.1136/bmjsrh-2017-200037
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive method use among women and its association with age, relationship status and duration: findings from the third British National Survey of Sexual Attitudes and Lifestyles (Natsal-3)

Abstract: BackgroundOne in six pregnancies in Britain are unplanned. An understanding of influences on contraceptive method choice is essential to provision compatible with users’ lifestyles. This study describes contraceptive method use by age, and relationship status and duration, among women in Britain.MethodsData from women participating in the third British National Survey of Sexual Attitudes and Lifestyles were used to describe contraceptive use grouped as: unreliable method or none; barrier methods; oral/injectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Such bias can result in under or over-reporting of sensitive sexual behaviours [13,20,21] but will not have affected estimates of prescribed contraceptive use based on dispensed prescription records. In keeping with GB and Ireland, we found that just over a quarter of women of reproductive age were dispensed prescribed contraceptives in any one year [9,[22][23][24].…”
Section: Findings and Interpretationsupporting
confidence: 64%
“…Such bias can result in under or over-reporting of sensitive sexual behaviours [13,20,21] but will not have affected estimates of prescribed contraceptive use based on dispensed prescription records. In keeping with GB and Ireland, we found that just over a quarter of women of reproductive age were dispensed prescribed contraceptives in any one year [9,[22][23][24].…”
Section: Findings and Interpretationsupporting
confidence: 64%
“…The prevalence of oral contraceptive pill use in 2008/2009 was 54% in women aged 20–24 years and 10% in 40–49 years in one survey, compared with 44% (442 per 1,000 women) using NLHC among women aged 20–24 years and 11% (106 per 1,000 women) in women aged 35–54 years, respectively, in our study ( S6 Fig ) [ 21 ]. In a large probability sample survey conducted in 2010 to 2012, 26% of women aged 16 to 24 were using hormonal methods (defined in the study as patches, pills, and injections), and 11% used LARC (implant, IUD, IUS) [ 22 ]. In our study, age-specific NLHC rates in 2011/2012 were 21% for women aged 13 to 19 and 41% for women aged 20 to 24.…”
Section: Discussionmentioning
confidence: 99%
“…Trip et al found that younger users may be less likely to use regular contraception due to a lack of ability to find suitable contraception 21. Firman et al explored the impact of nature and duration of relationship on preferred method of contraception and established that barrier methods were higher in short-term relationships among younger population 22. Pregnancy ‘risk’ perception and personal invulnerability may be potential factors influencing the use/non-use of contraception during sexual intercourse 23 24.…”
Section: Discussionmentioning
confidence: 99%